Enhancing Public Administration Strategies to Safeguard Pancasila Against Radicalist Threats - Aris Sarjito (Adabi : Journal of Public Administration and Business, 2024)
In Indonesia, Pancasila, the state ideology, is the foundation for national unity and identity. However, the principles of Pancasila face significant challenges from radicalist threats that seek to undermine its core values. This research aims to explore the key radicalist threats facing Pancasila, evaluate the effectiveness of current public administration strategies in addressing radicalism, and propose innovative approaches and policy recommendations to strengthen public administration strategies for defending Pancasila. Utilizing qualitative research methods, this study draws upon Social Identity Theory, Policy Implementation Theory, and Diffusion of Innovations Theory to analyze the multifaceted nature of radicalist threats and inform evidence-based policy decisions. Secondary data sources, including government reports, academic literature, and media sources, are employed to gain insights into radicalism's origins, manifestations, and impacts on Indonesian society. The results show how radicalist ideas are complicated and rooted in group identities. They also show how hard it can be to implement policies because of bureaucracy. Finally, they show how new ideas such as community engagement programs, educational reforms, and technological interventions might be able to effectively fight radicalism. By understanding these challenges and opportunities, policymakers can devise targeted interventions to safeguard Pancasila against radicalist threats, promoting democracy, social justice, and unity.